(untitled) (Agricultural Engineering, 2017)
The objective of the paper was to show various options of using by author an automated stand with computer image analysis for control of plant germination on the example of cauliflower Brassica oleracea L. ‘Pionier” variety. The developed system consisted of a mobile platform equipped with the acquisition and image processing system based on Raspberry PL processor. Germination of cauliflower seeds was the object of observation, which in one case were sown to soil after dressing them with plant extracts (sweet flag Acorus calamus L., great burdock roots Arctium lappa L.). In the other case, undressed seeds were sown in the place of previous application of the above-mentioned extracts. The use of a robot for monitoring plant germination enabled the automated analysis of the investigated material with higher frequency than it has been possible so far. Simultaneously, higher germination was reported when seeds were treated with macerates and extracts from great burdock roots.